The case of the Pseudo-hypercorrection - Jasper Doomen (Insights into Language, Culture and Communication, 2023)
This paper discusses a phenomenon I qualify as a pseudo-hypercorrection. A pseudo-hypercorrection has the same basis as a hypercorrection, but the important characteristic of a pseudo-hypercorrection that distinguishes it from a hypercorrection is that the expression is grammatically correct. As a case example I have used a phenomenon in Dutch, from the consideration that it occurs frequently, so that it cannot summarily be dismissed as a chance event.   Received: 17 January 2023 Accepted:27 March 2023 Published: 10 April 2023